Rapalink-1 Increased Infarct Size in Early Cerebral Ischemia–Reperfusion With Increased Blood–Brain Barrier Disruption - Chi, Oak Z.; Liu, Xia; Cofano, Sean; Patel, Nikhil; Jacinto, Estela; Weiss, Harvey R. (Frontiers in Physiology, 2021)
It has been reported that the mTOR pathway is involved in cerebral ischemia-reperfusion injury. One of the important pathological changes during reperfusion after cerebral ischemia is disruption of blood-brain barrier (BBB). Rapamycin, a first generation mTOR inhibitor, produces divergent effects on neuronal survival and alteration in BBB disruption. Here, we investigated how Rapalink-1, a third generation mTOR inhibitor, would affect neuronal survival and BBB disruption in the very early stage of cerebral ischemia-reperfusion that is within the thrombolysis therapy time window. Middle cerebral artery occlusion (MCAO) was performed in rats under isoflurane anesthesia with controlled ventilation. Two mg/kg of Rapalink-1 or vehicle was administered intraperitoneally 10 min after MCAO. After one hour of MCAO and two hours of reperfusion, the transfer coefficient (Ki) of 14C-α-aminoisobutyric acid (104 Da) and the volume of 3H-dextran (70,000 Da) distribution were determined to assess the degree of BBB disruption. At the same time points, phosphorylated S6 (Ser240/244) and Akt (Ser473) as well as MMP2 protein level were determined by Western blot along with the infarct size using tetrazolium stain. Rapalink-1 increased the Ki in the ischemic-reperfused cortex (+23 %), p < 0.05) without a significant change in the volume of dextran distribution. Rapalink-1 increased the percentage of cortical infarct out of the total cortical area (+41 %, p < 0.005). Rapalink-1 significantly decreased phosphorylated S6 as well as Akt to half the level of the control rats in the ischemic-reperfused cortex, which suggests both mTORC1 and mTORC2 were inhibited. The MMP2 level was increased suggesting that BBB disruption could be aggravated by Rapalink-1. Taken together, our data suggest that inhibiting both mTORC1 and mTORC2 by Rapalink-1 could worsen the neuronal damage in the early stage of cerebral ischemia-reperfusion and that aggravation of BBB disruption could be one of the contributing factors.